Optimization for vertical stabilizers on flutter stability of streamlined box girders with mountainous environment. Issue 2 (January 2020) - Guo, Junjie; Tang, Haojun; Li, Yongle; Wu, Lianhuo; Wang, Zewen
Wind environment in mountainous areas is very different from that in coastal and plain areas. Strong winds always show large angles of attack, affecting the flutter stability of long-span bridges which is one of the most important design factors. The central vertical stabilizer has been demonstrated to be an effective aerodynamic measure to improve the flutter stability, and this article optimizes the stabilizer to improve its applicability in mountainous areas. Computational fluid dynamics simulations are first performed to analyze the effects of stabilizers with different positions and forms on the flutter stability of an ideal box girder, and the aerodynamic mechanism is discussed based on the static and the dynamic flow fields, respectively. Wind tunnel tests are then carried out to test the critical flutter wind speed of a real box girder equipped with different stabilizers, and the change in its flutter stability is further analyzed. The results show that the vertical stabilizer with appropriate positions and heights can improve the participation level of structural heaving vibration, and thereby increases the flutter stability. At large angles of attack, the big vortex on the leading edge which may drive the bridge to flutter instability is gradually weakened with the increase in stabilizer's height. Compared with a single stabilizer, double vertical stabilizers, in the midst of which exists a negative pressure region, could achieve better effects.